The impact of crossfit training on strength, speed and some offensive handball skills for young people (Journal of the College of Basic Education, 2025)
Handball is a team game characterized by strength, speed in rhythm, constant exchange of Defense and attack. Attacks play a key role in determining the outcome of the match, as the goal is the decisive stage that culminates the team's effort and tactics. It represents the dividing point between winning and losing, which requires its implementation with the utmost concentration, with the greatest force and accuracy. It also highlights the importance of integrating CrossFit trainings with the characteristic of strength characterized by speed, because they have an effective effect in enhancing offensive skills, as these trainings contribute to improving the strength and accuracy of shooting, agility, and motor coordination, which enhances the efficiency of the offensive performance of young players, and supports their ability to implement skills with high efficiency in different playing situations preparing a training curriculum in the style of CrossFit trainings, The researcher also designed the experimental method as the most appropriate for the nature of the study, based on the design of one group with tight control, by conducting the two Tests before and after to measure the impact of the proposed training program. The research community was identified from the players of the students Sports Club, and the number of members of the sample amounted to (12) players who continued training during the period of application of the experiment , where they were selected by the method of intentional sample due to their suitability to the research conditions and objectives, and the researcher concluded that the CrossFit trainings prepared had an effective impact on the development of strength characterized by speed offensive skills of young handball players, the researcher also recommends using the CrossFit training method in the development of strength characterized by speed and offensive skill of handball players.